Good Jobs, Bad Jobs, No Jobs: Tough Choices for Canadian Labor Law - Adams, Roy J. (C.D. Howe Institute, 1995)
In many industrialized countries over the past twenty years, including Canada, the supply of "good" jobs for those with low formal education has declined relative to demand. While the contributors to this volume do not agree on which labor policies are best, they share a common dissatisifaction with the current way of doing things. –Publisher's description. Includes separate bibliographies at the end of most chapters.
Keywords: Labor market – Canada